Labor Market Institutions and Their Effect on Labor Market Performance in OECD and European Countries - Fialová, Kamila (World Bank, Washington, DC, 2016)
The aim of this technical note is to shed some light on relationship between labor market institutions and labor market outcomes in the member states of the Organization of Economic Cooperation and Development (OECD) in North America and East Asia; the New Member States of the European Union who are not members of the OECD (e.g. the Baltic states); countries in the European “Neighborhood” with aspire to accede to the EU (e.g. countries in the Western Balkans); and other European transitions countries (e.g. Ukraine, Moldova, and the Caucasus). Several estimation approaches for different data samples and explanatory variables were used to analyze the impact of labor market institutions on the labor market outcomes in European and OECD countries. This technical note, nevertheless, analyzes the impact of labor market institutions in above-mentioned regions and finds that they do affect major labor market indicators. The results show that the minimum wage tends to increase unemployment in non-European OECD sample, which is in accordance with the text-book pricing out effect. To examine the potential differences in the role of explanatory variables between the two OECD sub-samples the author applied modified Chow tests.The results of applied Chow tests examining the potential differences in the role of explanatory variables between the particular sub-samples are inconclusive. Generally, the author was not able to reject the hypothesis of stability of regression coefficients between the examined groups of countries in all tested models. While some of the estimated coefficients suggest different behavior, the available data did not allow to study this issue in detail.